Remaja sebagai Agen Pelapor dan Pelopor - Ida Sofiyanti; Heni Setyowati; Riva Mustika Anugrah (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2022)
Teenagers are the hope of a nation, a nation will become strong if it has teenagers who are smart, spiritual, intellectual and have strong spirits and emotions. The rapid development of the world is able to make a tendency for behavior change in adolescents, but this behavior change leads more to negative behavior. Adolescence is a transition from childhood, and usually will be faced with curiosity, trying many things. Adolescents, both boys and girls, will experience changes both psychologically and biologically. Society or parents still consider it taboo when talking about sexuality, this condition will actually make teenagers seek information on their own considering that it is now very easy to access sexuality sites. The results of the situation analysis at SMA N 01 Ampel Boyolali are that there is still a lack of students' knowledge about behavioral deviations in adolescents regarding sexuality, maturity of marriage age and nutritional status of adolescents. This service activity was carried out in 4 stages, namely the selection of groups of youth who were ready to become pioneer agents and election reporters. This election was managed by the counseling teacher, socialization to pioneer and reporting youth in this activity went smoothly and youth understood and understood the socialization given, after the outreach activities Pioneer youth and reporters carry out outreach and education to peers with assistance from guidance and counseling teachers, and the last stage is evaluating the usefulness of this activity, namely pioneering and reporting agents, namely they are very happy with this activity, because it can foster concern for fellow adolescents, proud of their new experience.ABSTRAKRemaja merupakan harapan sebuah bangsa, akan menjadi kuat sebuah bangsa jika memiliki remaja yang cerdas, spiritual, intelektual dan memiliki semangat dan emosi yang kuat. Perkembangan dunia yang sangat pesat mampu menjadikan kecenderungan perubahan perilaku pada remaja, akan tetapi perubahan perilaku ini lebih banyak mengarah kepada perilaku yang negatif. Remaja merupakan peralihan dari masa anak, dan biasanya akan dihadapkan kepada rasa ingin tahu, mencoba banyak hal. Remaja baik putra maupun putri akan mengalami perubahan baik secara psikis maupun biologis. Masyarakat ataupun orangtua masih memangggap tabu jika membicarakan tentang seksualitas, kondisi ini justru akan membuat para remaja mencari informasi sendiri mengingat sekarang mudah sekali mengakses situs-situs seksualitas. Hasil analisis situasi pada SMA N 01 Ampel Boyolali yaitu masih kurangnya pengetahuan siswa tentang penyimpangan perilaku pada remaja tentang seksualitas, pendewasaan usia perkawinan dan status gizi pada remaja. Kegiatan pengabdian ini dilaksanakan dalam 4 tahapan yaitu pemilihan kelompok remaja yang siap menjadi agen pelopor dan pelapor pemilihan ini dikelola oleh guru BK, sosialisasi kepada remaja pelopor dan pelapor pada kegiatan ini berjalan dengan lancar dan remaja paham dan mengerti akan sosialisasi yang diberikan, setelah kegiatan sosialisasi remaja pelopor dan pelapor melakukan sosialiasi dan edukasi kepada teman sebaya dengan pendampingan dari guru BK, dan tahap terakhir adalah evaluasi kebermanfaatan adanya kegiatan ini, yaitu agen pelopor dan pelapor yaitu mereka sangat senang dengan adanya kegiatan ini, karena bisa menumbuhkan kepedulian sesama remaja, bangga dengan pengalaman baru mereka.